Transmedia production and reception strategies in television in Colombia in recent years - Bustamante, Borys (2021)
This article presents the main results of the research project «Strategies for transmedia production and reception on television in Colombia 2014-2015. This research was carried out by the Education, Communication and Culture research group and its purpose was to analyze television fiction and the possibility of generating media and transmedia production processes in school settings. The research is an explorative and comprehensive diagnostic study of the communicative, educational, and cultural phenomena involved in the processes of innovation and transmediation of television fiction as well as the predominant uses and practices in young people enrolled in the school environment and in their daily lives and contexts. A mixed method was used in which the state of the art is carried out and the construction of a web page that collects the analyzes and creations made by the students of four public schools in Bogotá.